Studying some variables related to social capital of rural people in some villages of Kafr El-Sheikh Governorate – Egypt - Shabaan, Walaa Abdelatif; Hebish, Dalia Hassan; Elkholy, Amany Said (Journal of Humanities & Social Sciences, 2023)
The research aimed to identify the levels of social capital of the rural people in the selected research area, determining relationships between the studied independent variables and the degree of social capital, Determine the multiple relationships between the studied independent variables and the degree of social capital, Identify the variables that most contribute to explaining the variation in the degree of social capital of the respondents. 54.7% of the respondents in the middle level of the total social capital degree, Appositive significant correlation between degree of social capital and each of: years of education, years of respondent wife education, family monthly income, cultural openness, ambition level, attitude towards change, belonging to the local community, and satisfaction with services in the local community. Five independent variables contribute the most to explaining the variation in the degree of social capital, which are: belonging to the local community, cultural openness, level of ambition, number of family members and attitude towards change. The research recommends the need to introduce the concept of social capital for rural people in all sustainable development programs, because of its great role in advancing development, as one of the keys to the strategies of development plans and programs.
Keywords: Social Capital; Rural Society; Rural people